Towards a path dependence approach to study management innovation - Perello-Marin, Rosario M.; Marin-Garcia, Juan A.; Marcos Cuevas, Javier (Emerald Group Publishing Limited, 2013)
Purpose – Scholars in social sciences tend to use the term of path dependence without explaining exactly what they mean by it. Path dependence is a useful approach to understand the success or otherwise of the implementation of management innovation. The aim of this paper is to identify under which conditions it makes sense to talk about path dependence, and the relevance of using path dependence to the analysis of management innovation.Design/methodology/approach – The path dependence literature in different contexts and knowledge areas within social science is reviewed using a narrative approach.Findings – The concept of path dependence can be used to study management innovation, particularly when analyzing the introduction of new management practices. The authors argue that the order in which management practices are introduced has a profound effect on the outcomes for the organization. When the appropriate practices are introduced first, these create enhanced capabilities for the implementation of subsequent practices. If inappropriate practices are rolled out, they may severely impede management innovation and thus evolution and change of the firm.Research limitations/implications – This work highlights the need to conduct further research to understand the interaction between existing practices and the new ones. This study can be extended with an empirical work to corroborate the results presented here.Originality/value – By reviewing the different definitions of path dependence that exist in the literature, this paper will stimulate a debate on the necessary and sufficient conditions of path dependence and encourage a greater level of clarity in the management innovation area.